Improving the performance of carbon-based perovskite solar modules (70 cm2) by incorporating cesium halide in mesoporous TiO2 - Keremane, Kavya S. (2021)
We present the fabrication of highly efficient large-area carbon-based perovskite solar cells (C-PSCs) using CsX (X = Cl, Br, and I)-modified mesoporous (mp) TiO2 beads of 40 nm size as an electron transport material. Here, triple-layered scaffolds made of cesium halide-modified TiO2 exhibit efficient charge extraction as confirmed by enhanced photoluminescence quenching and inhibit the UV-activated degradation processes of perovskite, leading to an enhanced operational stability. Among the three cesium halide modifications, devices containing CsBr-modified TiO2 showed the highest short-circuit current density, yielding a photoconversion efficiency (PCE) of 12.59% of the device, with 0.7 cm2 active area and 11.55% for a large-area module (70 cm2). These devices are stable in an ambient atmosphere (25 °C, 65-70% RH) over 2700 h as well as at a high temperature (85 °C) over 750 h with virtually no hysteresis.